Optimization of cryoprotectant formulation to enhance the viability of Lactiplantibacillus plantarum NBC99 isolated from human origin - Kavak, Akif Emre; Zent, Inci; Ozdemir, Akin; Dertli, Enes (TAYLOR & FRANCIS INC, 2024)
Freeze drying has been well applied in the preparation of high-efficiency viability probiotic powders. However, the process is generally accompanied by probiotic viability deficiency, which poses a problem for further application. In this study, various kinds of cryoprotectant formulations (skim milk, maltodextrin, and sucrose) were tested to enhance the survival of Lactiplantibacillus plantarum NBC99 after freezing and freeze-drying. An I-optimal experimental design-oriented optimization model was presented to optimize the cryoprotective medium, and the highest cell survival was observed with 25% skim milk, 8.71% maltodextrin, and 1.13% sucrose cryoprotectant as the optimum condition. L. plantarum NBC99 has been a good potential strain for the manufacture of an industrial probiotic, and this research has aimed to investigate the long-term protective effects of optimum cryoprotectant formulations on the viability of bacteria. The results showed the potential value of freeze-dried probiotic L. plantarum NBC99 culture for commercialization.
Keywords: Cryoprotectant; I-optimal design; Lactiplantibacillus plantarum NBC99; probiotic; DRIED LACTOBACILLUS-PLANTARUM; STORAGE STABILITY; MILK; BULGARICUS; SURVIVAL; ENCAPSULATION; BACTERIA; POWDER; INULIN; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology